Since:
ax(2x + y - 5) = 6x^2 +3xy - 15x,
we should factor X out of the second equation to find out the value of a:
6x^2 + 3xy - 15x =
x(6x + 3y - 15),
Now that we factored X out, to find a, we need to find the other common factor:
(6x + 3y - 15) / (2x + y - 5),
which is 3.
Hence the value of a is 3
Answer:
x=1 and y=4/5
Step-by-step explanation:
<u>Given system of equations</u>
3x+5y=7
5x+10y=13
<u />
<u>Multiply first equation by 2</u>
2(3x+5y)=2(7)
6x+10y=14
<u>Eliminate y-variable to get "x"</u>
6x+10y=14
<u>- 5x+10y=13</u>
x = 1
<u>Substitute x=1 into either equation and find "y"</u>
3x+5y=7
3(1)+5y=7
3+5y=7
5y=4
y=4/5
Therefore, x=1 and y=4/5
Answer: 2.10
Step-by-step explanation: 2.10 * 4 + 6